2010
DOI: 10.1007/s11274-010-0312-z
|View full text |Cite
|
Sign up to set email alerts
|

Tripartite interactions among Paenibacillus lentimorbus NRRL B-30488, Piriformospora indica DSM 11827, and Cicer arietinum L.

Abstract: Tripartite interactions among Paenibacillus lentimorbus NRRL B-30488 (B-30488), Piriformospora indica DSM 11827 (DSM 11827) and their consortia (B-30488:DSM 11827:: 1:1) with native rhizobial population in the rhizosphere of Cicer arietinum L. (Chick pea) was tested for enhancing nodulations and plant growth promotion. Number of nodules and dry weight per plant significantly enhanced (P = 0.05), which is further evident by N, P, and K uptake by plants and were found to be maximum in B-30488 treated followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 38 publications
7
29
0
Order By: Relevance
“…Stem height increased by 43% and shoot length by 155%.This is in conformity to observations made in earlier investigations (Varma et al, 2001;Nautiyal et al, 2010;Bagde et al, 2010aBagde et al, , 2011.…”
Section: Resultssupporting
confidence: 92%
“…Stem height increased by 43% and shoot length by 155%.This is in conformity to observations made in earlier investigations (Varma et al, 2001;Nautiyal et al, 2010;Bagde et al, 2010aBagde et al, , 2011.…”
Section: Resultssupporting
confidence: 92%
“…Data are average value of three plants and following the analysis of variance (ANOVA) procedure, differences between desi PBG1 and kabuli BG1053 chickpea varieties, among different treatments and between varieties and treatments were determined using Critical difference from soil by native AMF and inoculated P. indica also might have benefited in development of efficient nodules in chickpea. Our results are in congruence with findings of Nautiyal et al (2010) who also demonstrated consortia of P.indica and PGPR enhanced the nodulation ability by native rhizobia in chickpea. On the contrary, Tavasolee et al (2011) reported that PGPR as bacterial strains have lowered nodule fresh mass due to competition for photosynthetic matter between bacteria and fungi in chickpea.…”
Section: Endophytic Dependency (Ed) %supporting
confidence: 92%
“…Significantly high N content was recorded in MR+PI+LPGPR1 (1.79 % and 1.85 %) followed byMR + PI + LK884 (1.77 % and 1.80 %) and MR+PI+LPGPR2 (1.73 % and 1.74 %) in desi PBG1 and kabuli BG1053, respectively over MR alone treatment. Improvement in total N content is well in line with previous findings in chickpea (Nautiyal et al 2010) and soybean (Lima et al 2011) where different bio-inoculant combinations as P.indica+PGPR, AMF+Azospirillum and Bradyrhizobium sp.+Glomus etunicatum, respectively. Higher P content was observed in P. indica alone treatment as compared to Mesorhizobium cicer alone.…”
Section: Endophytic Dependency (Ed) %supporting
confidence: 90%
See 1 more Smart Citation
“…Despite this strong indication of a direct contribution of P. indica to plant P nutrition, experimental results on agricultural crops have been inconsistent. While in tobacco, barley and green gram, colonization by P. indica did not increase P content of plants despite plant growth promotion (Barazani et al 2007;Achatz et al 2010;Ray and Valsalakumar 2010), chickpea and black lentil plants showed higher P content (Nautiyal et al 2010;Kumar et al 2012). This inconsistency may be partly explained by differences in experimental conditions (Fakhro et al 2010) and highlights the need for further research.…”
Section: Introductionmentioning
confidence: 99%